SOSIALISASI PENGENALAN LOGO OBAT DI DESA OLANGGATA KECAMATAN MOUTONG, KABUPATEN PARIGI MOUTONG - Mohamad Taufik Mokonu (LPPM Universitas Bina Mandiri Gorontalo, 2024)
This activity aims to increase the knowledge of pregnant women and the community in Olanggata Village, Moutong District, Parigi Moutong Regency, namely regarding assistance in administering iron supplement tablets It is hoped that these health cadres can pass on their knowledge to pregnant women so that they can reduce the level of nutritional anemia that occurs in olanggata Village. This service method is carried out in several stages. the first stage is to make observations with the government in the middle of Moutong village through the health cadres and the puskesmas, the second is preparation before leaving for the posyandu and coordinating with the health cadres and the puskesmas so tablets, the third is carrying out and carrying out assistance in administering tablets blood according to a predetermined schedule, and finally monitoring the results of activities. This activity was carried out on July 13 2023 at the Posyandu in Middle Moutong Village at 09.00-13.00 WIB and was attended by several Muslim women and health cadres as well as the puskesmas the results of the service obtained are able to provide positive and significant results. This can be seen from the significant mindset and attitude patterns of the community about the dangers of nutritional anemia caused by unhealthy lifestyles and habits that can increase the risk of exposure to disease and feel lazy to go to the posyandu.